A comprehensive characterization of culturable endophytic bacteria of Paris polyphylla and their potential role in microalgal growth in co-culture - Sonowal, Shashanka; Ahmed, Refad; Chikkaputtaiah, Channakeshavaiah; Basar, Egam; Velmurugan, Natarajan (Applied soil ecology : a section of Agriculture, ecosystems & environment, 2022)
Expanding endophytes of endangered medicinal plant Paris polyphylla can provide a means to study endo-symbiotic relationships with emphasis on different traits such as plant growth promotion (PGP), host-defence mechanism, and secondary metabolites production. As in many instances, endophytic isolates selected based on few traits fail when they are further screened for their direct role in plants. Therefore, in this study, we aimed to conduct comprehensive analyses on the under-explored endophytic bacterial community of P. polyphylla from the Himalayan mountains. Culture-dependent method was adapted to isolate under-explored endophytic bacterial community from the rhizomes of P. polyphylla. Isolates were identified using 16S rRNA gene sequencing and screened for different characteristics such as ability to grow in different temperatures, pH, and NaCl concentration, siderophore production, phosphate solubilisation, and plant cell wall-degrading enzymes production. Key genes such as sfp, ituD, and genes encoding for NRPS, and PKS clusters involved in particular traits were identified. A total of 186 endophytic isolates were characterized, and assigned to 4 major phyla Firmicutes, Gammaproteobacteria, Alphaproteobacteria, and Actinobacteria. The stringent methodology identified 7.52% and 2.15% of the isolates as siderophore producers and phosphate solubilisers respectively. Draft genome of the potential PGP endophyte Bacillus paralicheniformis PPE102 was obtained and investigated for various traits related to plant-microbe interactions. Co-culture experiments showed that PPE102 induced growth and had a positive impact on the biochemical content of photosynthetic microalga Micractinium sp. GA001. This debut attempt characterized exclusive collection of endophytic bacteria from P. polyphylla. This isolated community can be further explored for unique, and commercially-important biological compounds. •Culturable bacterial endophytes from endangered medicinal plant Paris polyphylla•Screened and characterized endophytic isolates in regard to different traits•Achieved in selection of candidate phenotypes with multiple trait characteristics•Determined draft genome of B. licheniformis PPE102 involved in different traits•PPE102 positively regulated growth and biochemical content of microalgae GA001.